2001
DOI: 10.1212/wnl.57.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Brain proton magnetic resonance spectroscopy in children exposed to methamphetamine in utero

Abstract: The authors found increased [Cr] in the striatum with relatively normal [NA] in children exposed to methamphetamine. These findings suggest an abnormality in energy metabolism in the brains of children exposed to methamphetamine in utero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 35 publications
2
72
0
Order By: Relevance
“…In human users, magnetic resonance imaging has shown long-term changes in various brain regions, including the hippocampus, following MA exposure either in adulthood or during in utero development (Smith et al 2001;Chang et al 2004;Thompson et al 2004). In animal studies, we have shown that the dentate gyrus and nucleus accumbens have a reduction in dendritic spines in adulthood when the animals were exposed to MA as neonates (Williams et al 2004a).…”
Section: Discussionmentioning
confidence: 95%
“…In human users, magnetic resonance imaging has shown long-term changes in various brain regions, including the hippocampus, following MA exposure either in adulthood or during in utero development (Smith et al 2001;Chang et al 2004;Thompson et al 2004). In animal studies, we have shown that the dentate gyrus and nucleus accumbens have a reduction in dendritic spines in adulthood when the animals were exposed to MA as neonates (Williams et al 2004a).…”
Section: Discussionmentioning
confidence: 95%
“…Cranial ultrasound studies of human newborns exposed to prenatal MA and cocaine demonstrated an increased incidence of intraventricular hemorrhage and white matter densities [14]. In addition, a study of MA-exposed children aged 3-16 years employing magnetic resonance spectroscopy demonstrated increased concentrations of creatine in the striatum suggesting a possible abnormality in energy metabolism in the brains of exposed children [40]. Volumetric assessments of magnetic resonance images in exposed children have demonstrated smaller subcortical volumes including the putamen, globus pallidus and hippocampus [11].…”
Section: Discussionmentioning
confidence: 99%
“…A neuroimaging study of 26 methamphetamine exposed (prenatal) and non-methamphetamine exposed children (128) suggested an abnormality in energy metabolism (increased creatine in the striatum) in the brains of children prenatally exposed to methamphetamine. These changes were not found to be associated with any increase in reported behavioural changes in the children.…”
Section: Chronic Effectsmentioning
confidence: 99%